Graduate employability: assessment of skills mismatch and wait-time of graduates in a Nigerian University (2010)
This tracer study assessed the issues of curriculum relevance and adequacy from the point of view of the graduates and their employers, this is with a view to ascertaining whether or not a gap exists in the content graduates were exposed to and the skills needed to perform effectively on the job. The sample for the study consisted of 805 graduates of the University of Ibadan between 1971 and 2008, and their empolyers. Two instruments: The Graduates' Questionnaire and Employers' Questionnaire were developed for data collection. Descriptive and inferential stastistics were used tol analysed the data. About 68% of the graduates were employed within one year of graduation, while less than 10% waited for over five years. The study found no clear-cut deficiences in the skills of the graduates. However, their employers rated the graduates higher in terms of efficiency at work, attitudes towards work, ability to take initiatives, possession of requisite skills to solve problems at work and so on than the graduates rated themselves on these attributes. Further study is needed to confirm these present findings.